2018
DOI: 10.1029/2018jg004550
|View full text |Cite
|
Sign up to set email alerts
|

Last Millennium Adélie Penguin Mortality and Colony Abandonment Events on Long Peninsula, East Antarctica

Abstract: The Adélie penguin (Pygoscelis adeliae) is sensitive to climatic and environmental changes, and paleoecological studies of Adélie penguins and their response to climatic forcing in maritime Antarctica usually address changes on long time scales. However, on Long Peninsula, East Antarctica, we identified numerous mummified Adélie penguin carcasses and phases of rapid sediment deposition at~750 and~200 years BP, indicating two multidecadal mass mortality events. Based upon chronological and sedimentary evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Notably, Gao et al (2018) also reported a phase of rapid deposition with increased sedimentary P concentrations, as well as mummified Adélie penguin carcasses dated to ~200 year BP, on Long Peninsula, East Antarctica, which was attributed to a period of anomalously intense precipitation. It is likely that such events are widespread around East Antarctica.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, Gao et al (2018) also reported a phase of rapid deposition with increased sedimentary P concentrations, as well as mummified Adélie penguin carcasses dated to ~200 year BP, on Long Peninsula, East Antarctica, which was attributed to a period of anomalously intense precipitation. It is likely that such events are widespread around East Antarctica.…”
Section: Resultsmentioning
confidence: 99%
“…Snow meltwater streams and rain can affect the survival success and eventually the penguin population (Chapman et al, 2011). Chicks die from hypothermia during extreme weather events (Gao et al, 2018; Ropert‐Coudert et al, 2015). Such streams affect the penguin subcolonies via the destruction of nests and the reduced rate hatching of eggs and survival of chicks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to discern intrusions of warm, moist air under a common AR framework opens up possibilities to study AR impacts on elds outside of the geosciences. For instance, there might be a link between ARs and penguin colony collapse as penguin colonies are highly sensitive to heavy, warm precipitation events (Gao et al [2018]). Rainfall can kill Adélie penguin chicks via hypothermia if they get wet since they lack waterproof plumage whereas heavy snowfall can bury eggs leading to penguin nest failure (Boersma and Rebstock [2014]; Ainley et al [2010]; Cimino et al [2014].…”
Section: Perspectivesmentioning
confidence: 99%